1999
DOI: 10.1007/s003830050521
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of venoarterial versus venovenous access in the cerebral circulation of newborns undergoing extracorporeal membrane oxygenation

Abstract: This study was designed to compare venoarterial (VA) with venovenous (VV) access in the cerebral circulation of newborn infants during extracorporeal membrane oxygenation (ECMO). Among 14 infants with VA ECMO, 7 had no intracranial complications (group 1), while the others (group 2) developed intracranial hemorrhage (ICH). In contrast, among 19 infants with VV ECMO, only 1 developed ICH. Serial echocardiograms were performed before and after 1, 6, 12, and 24 h and 2 and 3 days of ECMO. The mean cerebral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Fukuda et al demonstrated that VV ECMO had advantages in stabilizing brain hemodynamics compared with VA ECMO. 13 Roberts et al also recommended VV ECMO for neonatal respiratory failure in all cases, except where double lumen cannulation is impossible, or when septic shock is refractory to inotropic support. 14 Extracorporeal membrane oxygenation has been also used for the treatment of adults with severe respiratory failure since the 1970s, and two randomized trials showed no superiority of ECMO over conventional treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Fukuda et al demonstrated that VV ECMO had advantages in stabilizing brain hemodynamics compared with VA ECMO. 13 Roberts et al also recommended VV ECMO for neonatal respiratory failure in all cases, except where double lumen cannulation is impossible, or when septic shock is refractory to inotropic support. 14 Extracorporeal membrane oxygenation has been also used for the treatment of adults with severe respiratory failure since the 1970s, and two randomized trials showed no superiority of ECMO over conventional treatment.…”
Section: Discussionmentioning
confidence: 97%
“…This reduction persisted when re-evaluated 8 hours later. Fukuda et al (23) evaluated cerebral blood flow velocities in 14 infants on venoarterial ECMO and 19 infants on venovenous ECMO. These patients had a reduction from baseline values in bilateral MCA flow velocities during the 12 hours following cannulation for both venoarterial and venovenous ECMO, although the reductions were much more dramatic in the venoarterial group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Following ligation and cannulation of the internal jugular vein, patients on both venovenous and venoarterial ECMO experience increased cerebral venous congestion which may contribute to decreased CBFV in these patients (25, 26). Lastly, patients requiring venoarterial ECMO often have significantly reduced cardiac function (both ejection fraction and cardiac output) with cerebral blood flow then becoming primarily pump dependent (23). Pump flow is characterized by decreased systolic upstroke, lack of dichrotic notch, and continuous diastolic flow (22).…”
Section: Discussionmentioning
confidence: 99%
“…5–7 In both human and animal ECMO models, cerebrovascular injury appears to be more closely associated with reperfusion of ischemic cerebral tissue. 8 The porcine central nervous system, more specifically the brain, has been utilized as a proxy human model given similarities in size and anatomic characteristics. 9,10 More specifically, the pattern of piglet brain injury on coronary bypass approximates neonatal brain injury patterns and is localized to the neocortex and hippocampus.…”
mentioning
confidence: 99%